TEACHER SKILLS IN DEVELOPING INSTRUMENTS OF TEST ESSAY IN SCIENCE LESSONS IN JUNIOR HIGH SCHOOL: Case Study In Kediri, East Java-Indonesia - Laily Rosdiana; Martini Martini; Aris Rudi Purnomo; An-Nuril Maulida Fauziah (JURNAL PENA SAINS, 2019)
Assessment and evaluation must always be carried out. The evaluation process is one of the teacher's tasks that will determine the direction of the next learning process. Therefore, the teacher must be skilled in compiling the question test instrument, one of which is a matter of description. Regarding this objective, teachers need to be equipped with ways to prepare these instruments so that the quality of the questions made meets the standards and by the indicators of learning. Briefing on the science teachers MGMPs Kediri shows that teachers already have skills in preparing the description of the test instrument with a percentage of 53.12% about the level and 46.88% HOTS LOTS level. Based on the results, the skills of science teachers in Kediri District are not expectations.  The teachers must continue to practice in making the test instruments.